Analisis Risiko dan Faktor-Faktor yang Berpengaruh terhadap Produksi Usahatani Bawang Merah di Desa Sukorejo, Kecamatan Rejoso, Kabupaten Nganjuk - Ziana, Rafhani; Khoirunnisa, Tria Alfiatul; Suryandari, Ayu; Mazwan, M. Zul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Shallot (Allium cepa var. aggregatum) is a very important commodity in agriculture and the economy in Indonesia. Nganjuk Regency is recognized as the largest shallot producing center in East Java Province. The risk of shallot production can be influenced by factors such as land area, labor, fertilizer, and pesticides. This study aims to determine the level of production risk and analyze the factors that affect shallot production in Sukorejo Village, Nganjuk Regency. The research method uses risk analysis of the coefficient of variation and multiple linear regression analysis. The data used are primary data and secondary data obtained through observation, interviews, and the BPS website. The sample of farmers used was 30 respondents and selected by simple random sampling. The results show that the risk of shallot production in Sukorejo Village is high, with a coefficient of variation of 2.73. Onion production in this village is quite high, reaching an average of 5.77 tons with a productivity of 15.44 tons/ha. Factors such as land area, seeds, NPK fertilizer, organic fertilizer, pesticides, and labor simultaneously affect production. Partially, land area and NPK fertilizer play a significant role in shallot production.